Developing of a CTL-Based Project Approach Learning Model to Foster Environmental Awareness in Early Childhood Through the Student Field Experience Program (PLP) - Lathipah Hasanah; Sisca Nurul Fadila; Sepiana Permana Putri (PUSAKA: Journal of Educational Review, 2026)
This study aims to develop a Contextual Teaching and Learning (CTL) model based on the Project Approach to foster environmental care character through the PLP (School Field Practice) program for Early Childhood Islamic Education (PIAUD) students. The research utilized the Dick and Carey instructional design model as its developmental framework and employed a One Group Pretest-Posttest Design to evaluate model effectiveness. The study involved PIAUD students at UIN Syarif Hidayatullah Jakarta and partner early childhood education institutions (PAUD) located in South Tangerang as PLP sites. Expert validation yielded feasibility scores of 76.7% (content), 85.5% (learning model), and 90.9% (early childhood education), all falling within the highly acceptable category. Effectiveness testing produced an N-gain score of 0.78 (78%), indicating high effectiveness. These findings demonstrate that integrating a project-based CTL model within the PLP program significantly strengthens students capacity to design and implement character-oriented, environmentally conscious learning experiences, while simultaneously fostering observable pro-environmental behaviors in young children. The model thus offers a theoretically grounded and practically validated framework for embedding environmental character education within early childhood teacher preparation programmes.